Risks & benefits of foods: RiskBenefit4EU project and the case study involving mycotoxins and cereal-based foods - Assunção, Ricardo (2018)
Human diet may present both risks and benefits to consumers. Risk-benefit assessment (RBA) intends to estimate the benefits and risks for humans following exposure (or lack of exposure) to a particular food or food component and to integrate them in comparable measures. For instance, any policy action directed at the adverse effects also affects the degree of beneficial effects and vice versa. In the last years, a few number of European projects within the RBA of foods have been conducted and some challenges remained and new became apparent, however the RBA methodologies are far from being well established. In contrast, risk assessment (RA) within food safety is a well established discipline across the EU. In Portugal, a recent example is the RA study performed under MYCOMIX, a national funded project that studied the toxic effects of children exposure to multiple mycotoxins. MYCOMIX revealed a potential health concern associated to aflatoxins intake through the consumption of cereal-based foods with different contents of whole-grain. The output of this project also highlighted the knowledge gaps on the contrabalance beneficial health effect of these foods, and the need to determine the risk-benefit, since they are vehicles of food components that could be assumed as beneficial. “RiskBenefit4EU – Partnering to strengthen the risk-benefit assessment within EU using a holistic approach” is a recent European project funded by EFSA integrating a multidisciplinary team from Portugal, Denmark and France. This project aims to strengthen the EU capacity to assess and integrate food risks and benefits in the areas of microbiological, nutritional and chemical components through the development of a harmonized framework. To validate all the developed tools, a Portuguese case study on cereal-based foods, gathering data as mycotoxins and Bacillus cereus intake (risks) and the consumption of fibres (soluble/insoluble) (benefits) will be considered. RiskBenefit4EU will contribute for the development and the establishment of RBA as a tool to provide scientific evidence to inform risk management decisions in the area of food safety and nutrition.